2020
DOI: 10.3390/data5020042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Building Stock of Da Nang between 2015 and 2017

Abstract: This descriptor introduces a novel dataset, which contains the number and types of buildings in the city of Da Nang in Central Vietnam. The buildings were classified into nine distinct types and initially extracted from a satellite image of the year 2015. Secondly, changes were identified based on a visual interpretation of an image of the year 2017, so that new buildings, demolished buildings and building upgrades can be quantitatively analyzed. The data was aggregated by administrative wards and a hexagonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition, the actual size of the building shape can be a valuable proxy for the complexity of built-up structures. As reported by Warth et al (2020), including the number of corners in the analysis of buildings in the city of Belmopan effectively increased the detection of dwellings of low, middle, and high socio-economic status [111]. But shape can be defined in many more ways, for instance by the perimeter of the building footprint and its relation to the size (perimeter-area-ratio [150]).…”
Section: Building-related Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the actual size of the building shape can be a valuable proxy for the complexity of built-up structures. As reported by Warth et al (2020), including the number of corners in the analysis of buildings in the city of Belmopan effectively increased the detection of dwellings of low, middle, and high socio-economic status [111]. But shape can be defined in many more ways, for instance by the perimeter of the building footprint and its relation to the size (perimeter-area-ratio [150]).…”
Section: Building-related Parametersmentioning
confidence: 99%
“…In addition to density measures, distances are a suitable measure for urban morphology, not only between the buildings themselves, but also to the closest facilities or infrastructures [83]. Warth et al (2020) showed that the distance to the administrative city center was among the variables providing the highest contribution to the prediction of socio-economic conditions within the city of Belmopan [111]. Similarly, Jiang et al (2021) used the distance to the nearest urban center and the distance to the nearest railway station as a measure of human well-being [35].…”
Section: Continuous Spatial Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to the building types, socio-economic projections can be assigned to the single buildings, as described in the previous section. To avoid the impression of precision of the 15-point scale (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and a source of errors in the prediction of socio-economy, socio-economic points are aggregated into socio-economic classes (SEC). Besides reducing errors in predicting socio-economic information, it can be critical to publish detailed sensitive information regarding resident's socio-economic status at a single building level.…”
Section: Classification and Prediction Of Socio-economic Datamentioning
confidence: 99%
“…To increase the spatial resolution of the information and to retrieve qualitative information on the change that occurred between different acquisitions, Warth et al proposed a method to retrieve information on dynamics in building stock on a single building scale by differencing urban digital surface models (DSM) [16]. Braun et al [17] refined these results publishing a refined urban change dataset on single building scale for Da Nang, VN.…”
Section: Introductionmentioning
confidence: 99%